2020
DOI: 10.17212/1994-6309-2020-22.4-54-70
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cutting Dynamic on the Selection of the Technological Regimes to Ensure Minimal Wear of Cutting Tools

Abstract: Introduction. The intensity of tool wear, as an increment of wear to the cutting path, characterizes one of the important processing indicators. It is used in the development of algorithms for controlling the cutting process, including the calculation of trajectories in CNC machines. As the cutting speed increases, there is a value at which the wear rate is minimal. It corresponds to the optimal value of heat production in the cutting zone, that is, the power of irreversible transformations of the energy suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Therefore, even their small variations can correspond to different diagrams of wear and changes in the geometric characteristics of the surface formed by cutting. As our studies show, all evolutionary diagrams are characterized by the development of chaotic dynamics, so there is a limit cutting path after which machining is impossible [35], [36]. Consequently, all the output characteristics of the process, including the geometric topology and wear, evolve to their terminal state due to the energy of irreversible transformations.…”
Section: Desired Attractor Constructionmentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, even their small variations can correspond to different diagrams of wear and changes in the geometric characteristics of the surface formed by cutting. As our studies show, all evolutionary diagrams are characterized by the development of chaotic dynamics, so there is a limit cutting path after which machining is impossible [35], [36]. Consequently, all the output characteristics of the process, including the geometric topology and wear, evolve to their terminal state due to the energy of irreversible transformations.…”
Section: Desired Attractor Constructionmentioning
confidence: 90%
“…In contrast to existing ideas about the existence of an optimal cutting speed, but unchanged along the trajectory, the performed research shows that it is necessary to consider the optimal trajectory along the work done by cutting, that is, along the displacement. In addition, tool wear depends on the parameters of the dynamic system and, first of all, uncontrolled vibration disturbances [36]- [37]. 4) Each type of phase space topology corresponds to its own skeleton geometric surface topology (Fig.…”
Section: Dynamic Peculiarities and Control And Dynamics Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Presented in the article materials allow explaining the experimental investigations carried out during the last thirty years in the direction of evolution of the dynamic friction system. They are described in detail in monographs [10], [14], [36], [38] and articles [15], [22], [29], [30]. Let us briefly consider the results of the experimental study of the vibration characteristics of contacting pairs during the development of their wear.…”
Section: Fig 4 Examples Of Trajectories In Phase Space Sections Depending On the Work Done By Friction Forcesmentioning
confidence: 99%
“…At the same time, it is shown that vibrations affect the wear rate of the contacted pairs [29]- [31]. It was the change in the vibration properties of the friction unit depending on the state of the tribo-medium that led to the development of the direction in tribo-technology, which con-sists in the creation of systems for vibration diagnostics of friction processes [30]- [33].…”
Section: Introductionmentioning
confidence: 99%